PENERAPAN MODEL PEMBELAJARAN BERBASIS MASALAH UNTUK MENINGKATKAN HASIL BELAJAR IPS SISWA KELAS IV SD NEGERI 29 PEKANBARU - Wenny Shaputri; Hendri Marhadi; Zariul Antosa (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2018)
Abstract: This research was conducted because of the low of IPS study result of fourth grade students of elementary school 29 Pekanbaru, criterian minimum determined in school, that is 75. Of 30 students, reaching criterian minimum only 18 students (60%), while students who have not reached criterian minimum is 12 students (40%) with a grade point average of 70.26. To solve the problem, the researcher applied problem based learning model. The purpose of this study is to improve the learning outcomes of IPS students of fourth grade elementary school 29 Pekanbaru with the application of problem-based learning model. The data analyses result of research got the average score of base score 70,26 increase in cycle I equal to 6,74% to 75. In cycle II average value of student also experience increase equal to 14,57 become 80,5. At the first score of clotical learning at fourth grade on social science is 40% (not complete). After applied problem-based learning model in cycle I, student's clasical completeness increased to 83,33% (unfinished) and in cycle II, student's clasical completeness increased by 100% (complete). Teacher activity at the first learning of the first cycle of the percentage is 60% with sufficient category. At the second learning it increased to 80% with good category. At the first learning of cycle II teacher activity to 90% with very good category. At the second meeting to be 95% with very good category. Student activity at first meeting of cycle I the percentage is 60% with enough category. The second learning increased to 80% with good category. At the first learning of cycle II student activity increased to 90% with very good category. At the second learning to be 100% with very good category. From this research can be concluded that by applying problem-based learnining model can improve learning result of social science subject at the fourth grade of elementary school 29 pekanbaru.Keywords: Problem-based learning , Social studies outcomes